Utilização de descritores morfológicos e moleculares na caracterização da divergência genética de linhagens de milho - Montecelli, Alfredo Vieira (2011)
The analyses of genetic divergence, through predictive methods have been used as a criterion for the choice of parents in plant breeding programs. The objectives of the study were to estimate the genetic divergence among maize lines using morphological and molecular data, using multivariate analysis, check the relationship of these procedures and correlate the clusters formed with heterotic groups previously established by usual method topcross. The experiment was carried out at the Cooperativa Central de Pesquisa Agrícola (Coodetec), in Cascavel / PR, the field experiment was conducted in 2009/10, evaluating a set of 46 elite maize lines. We assessed 10 morphological traits and used 44 SSR molecular markers to estimate the distance of matrix Euclidean measure for the cluster analysis. Cluster analysis showed the genetic divergence between maize lines. The cophenetic correlation coefficient was providing adequate assessment of groups, however, little agreement between the clustering methods with the previously formed heterotic groups could be observed. Thus, the combined use methods taking into account morphological and molecular enable realizations or further inferences, thus becoming relevant information in planning combinations for maize crosses.